Experimental Evaluation and Vibration Response Simulation of Electric Motor Base Structure Through Direct Frequency Response Method Using MSC Patran 2005 - Wayan Adisaputra, I
In this study a finite element model of an electric motor supporting structure is developed using MSC Patran 2005. It is intended to evaluate the vibration response of the supporting structure using direct frequency response method available in this package software. A normal modes analysis is conducted to the developed finite element model and the results are validated by measuring the structure Frequency Response Function. Based on valid finite element model, vibration response of the finite element model due to harmonic excitation force is evaluated using direct frequency response method. The results are compared to the supporting structure vibration responses which are measured experimentally using an electrodynamic exciter as an excitation force. The finite element model then used to predict vibration response caused by residual unbalance force on rotating electric motor mounted on the supporting structure. The vibration responses obtained using FEM model are compared to the experimental results. The comparison results show 1,79% minimum error occurred for 20,5 Hz at measuring point number 2. The maximum error of 75,23% occurred on point number 5 for 25,5 Hz which closes to one of its natural frequencies.